Caste, class, and power changing patterns of stratification in a Tanjore village - Beteille, Andre (Oxford University Press, 2012)
Andre Beteille's Caste, Class and Power has grown out of his fieldwork in Sripuram in Thanjavur District, Tamil Nadu. The book's main strengths are the clarity of its descriptive analysis of the three caste groups and agrarian classes, as well as the interactions between them; and the force of its theoretical argument about the relationship between the caste structure, the class system and the distribution of political power. Its thesis about correspondence among the caste, class and political systems is considerably less convincing for the middling majority than for either the Brahmins or Adi-Dravidas. It is also an important historical source about the social structure of Indian villages in the early decades following Independence. Additionally, it is a model of ethnographic and theoretical analysis.